Efektivitas Trichoderma sp. yang Ditambahkan pada Kompos Daun untuk Pengendalian Penyakit Layu Fusarium pada Tanaman Stroberi (Fragaria sp.) di Desa Pancasari Kabupaten Buleleng - SONIA ASHA HASARI; I GEDE RAI MAYA TEMAJA; I PUTU SUDIARTA; GUSTI NGURAH ALIT SUSANTA WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Affectivity of Trichoderma sp. that Added in Leaf Compost to Control Fusarium Wilt Diseases on Strawberry Plants (Fragaria sp.) in Pancasari Village Buleleng RegencyThis research purpose in order to find the best concentrations of Trichoderma sp. which is added into the leaf compost to control fusarium wilt disease on strawberry plant. This research was conducted on December 2017 to March 2018 in Plant Diseases Laboratory of Udayana University and Pancasari Village, Sukasada District, Buleleng Regency. The experimental design used a Randomized Block Design (RBD) with six treatments and four replications, for each treatment consists of ten plant units. Observation variables in this research are disease percentage, Trichoderma sp. population on the ground, plant height, yield, and the weight of plants. The results showed that Trichoderma sp. treatment which were added into leaf compost is more effective to control the fusarium wilt diseases on strawberry plants rather than control treatments. P5 is the best treatment as it has the lowest disease percentage for around 20%, stimulate the highest growth of the plants into 25.8 cm, and has the highest yields 187 g.